Pengaruh Perbandingan Performa pada Motor Yamaha Mx King 180cc dengan Ecu Standar dan Ecu Racing - Arya Putra Nugraha; Farda Pega Libra Gojandra; Rizqi Fitri Naryanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research is motivated by the development of injection motorcycle engine management system technology that demands increased performance through optimization of the Electronic Control Unit (ECU). This study aims to analyze the performance comparison of the Yamaha MX King 180 cc using a standard ECU and a racing ECU on engine power and torque. The method used is an experiment with engine dynotest testing in the range of 6000-10000 RPM. The research sample is a 2015 Yamaha MX King unit that has been modified to 180 cc. Data were collected through direct measurements of power (HP) and torque (Nm), then analyzed descriptively in the form of tables and graphs. The results show that the racing ECU is able to produce a higher maximum power of 24.9 HP at 10000 RPM compared to the standard ECU of 22.2 HP at the same engine speed. In terms of torque, both types of ECU reach peak values ​​at 8000 RPM with a relatively small difference (18.18 Nm on the standard ECU and 18.15 Nm on the racing ECU). However, at low to mid-range revs, the racing ECU tends to produce slightly more torque, although at very high revs, it experiences a greater decrease compared to the standard ECU. The racing ECU excels at increasing high-rev power, while the standard ECU exhibits more consistent torque stability. Therefore, the choice of ECU type must be tailored to the performance requirements and the characteristics of the vehicle's use.